Basel accord and financial intermediation: The impact of policy - Martin Berka; Christian Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper studies loan activity in a context where banks must follow Basel Accord-type rules and acquire financing from households. Loan activity typically decreases when entrepreneurs' investment returns decline, and we study which type of policy could revigorate an economy in a trough. We find that active monetary policy increases loan volume even when the economy is in good shape; introducing active capital requirement policy can be effective as well if it implies tightening of regulation in bad times. This is performed with an heterogeneous agent economy with occupational choice, financial intermediation and aggregate shocks to the distribution of entrepreneurial returns.
Keywords: E44; E22; G28; E58; 330; bank capital channel; capital requirements; Basel Accord; occupational choice; bankruptcy; credit crunch; Basel II; Kreditrationierung; Finanzintermediär; Konkurs; Theorie